PENERAPAN STANDAR PEMENUHAN KEBUTUHAN HIDUP LAYAK DI KECAMATAN TANJUNG REDEB: PENERAPAN STANDAR PEMENUHAN KEBUTUHAN HIDUP LAYAK DI KECAMATAN TANJUNG REDEB - IRA I (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2020)
The purpose of the research carried out was to determine whether the average level of fulfillment of the Decent Living Needs Standard in Tanjung Redeb District was significantly above the Decent Living Needs (KHL) of Berau Regency in 2020. Based on the research results, it can be seen that the t test at the confidence level of 95% and the degrees of freedom of n-1, it is known that the t value (th) is -1.403 while the t value in the table is 1.697. Because the t value is smaller than the t value in the table (th <tt), thus the hypothesis obtained by the author turns out that the fulfillment of the Decent Living Needs Standard in Tanjung Redeb District is already below the Decent Living Needs (KHL) of Berau Regency in 2020. The average income of 30 Sari Laut traders in Tanjung Redeb District, Berau Regency is Rp. 2,733,000, - per month with a standard deviation of Rp. 1,512,222, - from the average value of his income. In general, the fulfillment of the Decent Living Needs Standard in Tanjung Redeb District is still below the Decent Living Needs (KHL) of Berau Regency in 2020.